Manganese / cobalt bimetallic loaded nitrogen-doped carbon material, preparation method thereof and application of manganese / cobalt bimetallic loaded nitrogen-doped carbon material in photocatalytic CO2 reduction

By preparing manganese/cobalt bimetallic supported nitrogen-doped carbon materials, the problems of difficult electron-hole separation and insufficient active sites in photocatalysts were solved, achieving efficient CO2 conversion and high-yield CO generation.

CN121372471APending Publication Date: 2026-01-23BEIJING UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511902526.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-17
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Existing nanomaterial photocatalysts suffer from low catalytic efficiency due to the difficulty in separating photogenerated electrons and holes and insufficient active sites during photocatalytic CO2 reduction.

Method used

Using a manganese/cobalt bimetallic catalyst, a highly dispersed manganese/cobalt core-shell structure was prepared by loading nitrogen-doped carbon material. The electronic structure was optimized by utilizing the synergistic effect and charge transfer of the bimetallic catalyst to enhance the adsorption and activation capacity of CO2.

Benefits of technology

It achieved highly efficient CO2 conversion, with CO selectivity approaching 100% and CO yield reaching 814 μmol/g/hour, significantly improving the photocatalytic performance of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121372471A_ABST
    Figure CN121372471A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation and photocatalysis of MOF (Metal Organic Framework) derivative materials, in particular to a manganese / cobalt bimetallic loaded nitrogen-doped carbon material as well as a preparation method and application thereof in photocatalytic CO2 reduction. According to the invention, the manganese / cobalt bimetallic catalyst MnCo-NC is obtained by taking a metal-doped Mn-ZIF (at) Co-ZIF imidazole zeolite skeleton as a precursor through derivation. Through the synergistic effect of Mn and Co, the electronic structure of the catalyst can be optimized, a plurality of adsorption sites are provided, and strong interaction with CO2 molecules is formed, so that the CO2 adsorption and activation capability is enhanced. The catalyst provided by the invention shows excellent performance in photocatalysis of high-purity CO2 (the volume fraction is greater than 99.999%), and CO selectivity close to 100% and CO yield of 814 micromole / g / hour can be realized in 0.01 Mpa atmosphere and a triethylamine and water system.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of preparation of MOF derivative materials and photocatalysis technology, and particularly relates to a manganese / cobalt bimetallic loaded nitrogen-doped carbon material, a preparation method thereof and application of the material in photocatalytic CO2 reduction. BACKGROUND

[0002] Photocatalytic CO2 conversion is a promising technology that can convert CO2 into high-value chemicals such as methanol, ethanol, formic acid, and other fuels and chemical raw materials. This process not only reduces CO2 emissions and alleviates global warming, but also realizes the recycling of carbon resources and provides a new way for sustainable energy development, thus attracting great attention.

[0003] However, most nano-material photocatalysts exhibit limited activity in practical applications. These catalysts usually have strong bound excitons, that is, the interaction between photo-generated electrons and holes is strong, making it difficult to separate and migrate to the catalyst surface to participate in the reaction. At the same time, they have insufficient active sites, which cannot provide enough space for the adsorption and conversion of CO2 molecules, resulting in low catalytic efficiency and only moderate activity. In recent years, highly dispersed single-metal catalysts have attracted widespread attention in various catalytic reactions including photocatalytic CO2 conversion due to their fully exposed active sites. Single-metal catalysts have unique structural and performance characteristics. On the one hand, they maximize atomic utilization, with almost every metal atom serving as an active center to participate in the catalytic reaction, greatly improving the intrinsic activity of the catalyst. On the other hand, the active sites exist in isolation, avoiding the agglomeration of metal atoms, so that each active site can function independently, and there are various single-metal species with specific functions, which can be selected and designed according to different catalytic needs.

[0004] Although the highly dispersed single-metal catalyst has many advantages, it is still a pressing challenge to integrate these representative advantages into bimetallic and regulate the synergistic photocatalysis. The biggest advantage of bimetallic catalyst is that the photocatalytic activity can be enhanced by integrating the bifunctional characteristics and adjusting the synergistic effect. In particular, the bimetallic catalyst exhibits unique advantages in the photocatalytic CO2 reduction reaction. By the participation of two metals, it not only exposes more reaction sites, increases the contact opportunity of CO2 molecules with the catalyst surface, but also forms a reaction center with high electron / hole density. These metal atomic centers with different electron / hole densities as active sites of redox reaction can promote the transfer of electrons and holes, accelerate the adsorption, activation and conversion process of CO2 molecules. At the same time, the built-in electric field between the two metals can act as a driving force to promote the effective separation and transfer of photo-generated charges, reduce the recombination probability of electron-hole pairs, and thus improve the photocatalytic efficiency of the catalyst, showing great potential for CO2 conversion. SUMMARY

[0005] In view of the problems in the prior art, the application provides a preparation method of a manganese / cobalt bimetallic catalyst and its application in photocatalytic CO2 reduction. The high dispersion of the metal helps to highly expose the catalytically active sites, and the active site density of the bimetallic catalyst is higher, and has a synergistic effect. Through effective charge transfer, a special electronic structure is formed, which has stronger adsorption capacity and activation effect on CO2 molecules, and is expected to realize efficient conversion of CO2.

[0006] To achieve the above-mentioned purpose, the application provides the following technical solutions: The application provides a preparation method of a manganese / cobalt bimetallic catalyst, comprising the following steps: (1) Dissolve a soluble zinc salt, a soluble manganese salt and 2-methyl imidazole in water, and then centrifuge, wash and dry after stirring to obtain a Mn-ZIF core; (2) Disperse the obtained Mn-ZIF core in methanol, add 2-methyl imidazole methanol solution and a mixed methanol solution of soluble zinc salt and soluble cobalt salt, and then crystallize at room temperature after stirring, separate, wash and dry to obtain a Mn-ZIF@Co-ZIF manganese / cobalt bimetallic core-shell structure metal organic framework material; (3) Use the Mn-ZIF@Co-ZIF as a template to perform high-temperature pyrolysis, acid washing, centrifugal drying to obtain a highly dispersed manganese / cobalt loaded on nitrogen-doped carbon MnCo-NC.

[0007] Preferably, in step (1), the molar ratio of the zinc salt to the ligand is 1:6; and the molar ratio of the manganese salt to the zinc salt is 1:100. The low doping of manganese is ensured to avoid agglomeration, and the self-assembly of Zn ions and ligands is controlled, and at the same time, a trace amount of Mn2+ The manganese is uniformly doped in the ZIF framework. If the doping amount of manganese is too high, high-dispersion active sites cannot be obtained, and the ZIF framework is difficult to form.

[0008] Preferably, the stirring temperature is 25℃, and the stirring time is 2h. Under this condition, stable crystal structure can be ensured.

[0009] Preferably, the zinc salt is at least one selected from Zn(NO3)2·6H2O, ZnCl2, ZnSO4·7H2O and Zn(CH3COO)2·2H2O; The manganese salt is at least one selected from Mn(NO3)2·4H2O, MnCl2, MnSO4·4H2O and Mn(CH3COO)2·4H2O; The centrifugal separation speed is 5000-10000 rpm, and the time is 1-15 min. The drying temperature is 60-120℃, and the drying time is 12-48h.

[0010] Preferably, the molar ratio of the cobalt salt and the zinc salt in S2 is 1:75-125, and the addition amount ratio of the ZIF-L(Mn) precursor and 2-methylimidazole is 0.1g:3mmol.

[0011] Preferably, the stirring temperature in S2 is 25℃, the stirring time is 20 min, and the crystallization reaction time is 24h. Under this condition, the Co-ZIF can be induced to grow epitaxially on the surface of the Mn-ZIF.

[0012] Preferably, the zinc salt is at least one selected from Zn(NO3)2·6H2O, ZnCl2, ZnSO4·7H2O and Zn(CH3COO)2·2H2O; The cobalt salt is at least one selected from Co(NO3)2·6H2O, CoCl2·6H2O, CoSO4·7H2O and Co(CH3COO)2·4H2O; the centrifugal separation speed is 5000-10000 rpm, and the time is 1-15 min; the drying temperature is 60-120℃, and the drying time is 12-48h.

[0013] Preferably, the high-temperature pyrolysis atmosphere in S3 is nitrogen or argon; the pyrolysis temperature is 850-1000℃; the heating rate is 3-7℃ / min; and the holding time is 2-5h. Slow heating can avoid structure collapse, graphitization of the carbon framework and formation of metal active sites.

[0014] The application also provides the manganese / cobalt loaded nitrogen-doped carbon material prepared by the preparation method.

[0015] The application further provides application of the manganese / cobalt loaded nitrogen-doped carbon material prepared by the preparation method in photocatalytic reduction of CO2.

[0016] The beneficial technical effects of the application are as follows: (1) The manganese / cobalt bimetallic catalyst MnCo-NC is derived from the metal-doped Mn-ZIF@Co-ZIF imidazole zeolite framework as a precursor. The synergistic effect of Mn and Co can optimize the electronic structure of the catalyst, and the bimetallic active center can provide multiple adsorption sites to form a stronger interaction with CO2 molecules, thereby enhancing the adsorption and activation capacity of CO2.

[0017] (2) The catalyst provided by the application exhibits excellent performance in photocatalytic high-purity CO2 (volume fraction > 99.999%). In a 0.01 Mpa atmosphere and a triethylamine / water system, the highly dispersed manganese / cobalt loaded in the nitrogen-doped carbon catalyst MnCo-NC can achieve a CO selectivity close to 100% and a CO yield of 814 micromole / g / hour.

[0018] (3) The single-metal system only needs to regulate the dispersion of a single metal, but the manganese and cobalt atoms in the bimetallic system are prone to migrate and agglomerate at high temperatures to form large particles without activity (such as Co-NPs generated when Co:Zn = 1:25 in the comparative example). The present application breaks through this obstacle through a confined growth strategy: first synthesizing a Mn-ZIF core and then epitaxially growing a Co-ZIF layer, so that the two metal atoms are physically isolated by the ZIF framework, so that they are uniformly dispersed during high-temperature pyrolysis, and then high-dispersion active sites are formed.

[0019] (4) The present application realizes atomic-level synergy through directional epitaxial growth and pyrolysis bonding; the uncoordinated Zn on the surface of Mn-ZIF 2+ induces the epitaxial growth of Co-ZIF, and the Co-ZIF particles are uniformly anchored on the leaf-shaped Mn-ZIF surface. BRIEF DESCRIPTION OF DRAWINGS

[0020] Figure 1 X-ray powder diffraction pattern of Mn-ZIF@Co-ZIF obtained in Example 1.

[0021] Figure 2 Scanning electron microscope image of Mn-ZIF@Co-ZIF obtained in Example 1.

[0022] Figure 3 X-ray powder diffraction pattern of MnCo-NC obtained in Example 1.

[0023] Figure 4 High-resolution transmission electron microscope image of MnCo-NC obtained in Example 1.

[0024] Figure 5 X-ray electron spectrogram of MnCo-NC obtained in Example 1.

[0025] Figure 6 Photocatalytic performance graph of MnCo-NC obtained in Example 1 under high-purity CO2.

[0026] Figure 7 Comparison graph of photocatalytic performance of MnCo-NC and physically mixed Mn-CN+Co-CN under high-purity CO2. DETAILED DESCRIPTION

[0027] Example 1 S1, Preparation of Mn-ZIF precursor material 2mmol Zn(NO3)2·6H2O and 0.02mmol Mn(NO3)2·4H2O were added to 40mL of deionized water to obtain solution A; 12mmol of 2-methylimidazole was added to 40mL of deionized water to obtain solution B. Solution B was quickly poured into solution A, stirred at room temperature for 2 hours, the product was collected, washed, centrifuged at a speed of 5000-10000 rpm for 1-15 minutes, dried at a temperature of 60-120℃ for 12-48 hours to obtain a white product Mn-ZIF.

[0028] S2, Preparation of Mn-ZIF@Co-ZIF composite material (1) 0.4g of Mn-ZIF precursor material and 12mmol of 2-methylimidazole were dispersed in 25mL of methanol to obtain solution C; (2) 3mmol of Zn(NO3)2·6H2O and 0.04mmol of Co(NO3)2·6H2O were weighed and dissolved in 25mL of methanol to obtain solution D; solution D was quickly poured into solution C, stirred for 20 minutes, and crystallized for 24 hours. The product was collected, washed, centrifuged and dried to obtain a light purple product, Mn-ZIF@Co-ZIF composite material.

[0029] S3, Preparation of MnCo-NC Mn-ZIF@Co-ZIF was placed in a tube furnace, heated to 920℃ under argon atmosphere, with a heating rate of 3℃ / min; kept for 3 hours to obtain a black product, which was washed with 1.0mol / L HCl, centrifuged and dried to obtain MnCo-NC.

[0030] Example 2 The difference between Example 2 and Example 1 is that the pyrolysis atmosphere is nitrogen, the pyrolysis temperature is 950℃, the heating rate is 5℃ / min, and the holding time is 4 hours, and the rest of the conditions are exactly the same.

[0031] Example 3 Example 3 and Example 1 are different in that the high-temperature pyrolysis atmosphere is argon, the pyrolysis temperature is 850°C, the heating rate is 7°C / min; the holding time is 5 hours, and the rest of the conditions are exactly the same.

[0032] Example 4 Example 4 and Example 1 are different in that the high-temperature pyrolysis atmosphere is argon, the pyrolysis temperature is 1000°C, the heating rate is 7°C / min; the holding time is 2 hours, and the rest of the conditions are exactly the same.

[0033] The materials obtained in Examples 1-4 are the same, and the obtained materials are characterized, and the results are as follows: Figure 1 The X-ray powder diffraction pattern of Mn-ZIF@Co-ZIF: The composite material shows the characteristic diffraction peaks of Mn-ZIF-L and Co-ZIF-8 at the same time, which confirms the successful synthesis of Mn-ZIF@Co-ZIF composite material.

[0034] Figure 2 The scanning electron microscope image of Mn-ZIF@Co-ZIF: Co-ZIF particles are uniformly and dispersedly distributed on the surface of two-dimensional leafy Mn-ZIF-L material, which confirms the successful compounding of Mn-ZIF@Co-ZIF composite material.

[0035] Figure 3 The X-ray powder diffraction pattern of MnCo-NC: The characteristic peaks of ZIF-L and ZIF-8 disappear after carbonization, and the diffraction peak at about 2 θ =26° indicates the formation of graphitic carbon structure, and the weak diffraction peak at 2 θ =44.5° can be attributed to the cobalt nanoparticles corresponding to the (111) crystal face.

[0036] Figure 4 The high-resolution transmission electron microscope image of MnCo-NC: It presents graphitized structure, showing graphitic carbon layers and dispersed metal particles, and the agglomerated particles may be attributed to the accumulation of a small number of Co particles, and Figure 3 The diffraction peak at 2 θ =44.5° matches.

[0037] Figure 5 The X-ray energy spectrum analysis diagram of MnCo-NC: It is found that Mn, Co, C, N four elements are uniformly distributed in the leaf shape.

[0038] The MnCo-NC material is tested for catalytic performance Take 5 mg of the above MnCo-NC photocatalyst, 3 mL of acetonitrile, 2 mL of water, 1 mL of triethylamine, and a 300 W xenon lamp as the light source for the photocatalytic experiment. The high-purity CO2 (99.999%) is filled to a pressure of 0.1 MPa, and then the light is irradiated (the light irradiation intensity is 150 mW / cm 2 ). The samples are taken at 0.5, 1, 1.5, 2, and 2.5 hours, respectively, and the results are analyzed by gas chromatography. The CO yield at 1 hour is calculated, and the results are shown in Figure 6 . The yield is 814 micromoles per gram per hour, which is 5.4 times that of the monomer Mn-NC and 2.2 times that of the monomer Co-NC. Take 5 mg of the physical mixture of Mn-CN and Co-CN (1:1) and test it under the same light conditions. The results are analyzed by gas chromatography at 2.5 hours, and the CO yield at 2.5 hours is calculated. The results are compared with those of the in-situ grown MnCo-CN, and the results are shown in Figure 7 . The CO yield of the in-situ grown MnCo-CN is much higher than that of the physical mixture of Mn-CN and Co-CN.

[0039] Example 7 The difference between Example 7 and Example 1 is that the molar ratio of cobalt salt to zinc salt in S2 is 1:100, i.e., the amount of Zn(NO3)2·6H2O added is 4 mmol, and the rest of the conditions are exactly the same.

[0040] Example 8 The difference between Example 8 and Example 1 is that the molar ratio of cobalt salt to zinc salt in S2 is 1:125, i.e., the amount of Zn(NO3)2·6H2O added is 5 mmol, and the rest of the conditions are exactly the same.

[0041] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the molar ratio of cobalt salt to zinc salt in S2 is 1:25, i.e., the amount of Zn(NO3)2·6H2O added is 1 mmol, and the rest of the conditions are exactly the same.

[0042] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the molar ratio of cobalt salt to zinc salt in S2 is 1:50, i.e., the amount of Zn(NO3)2·6H2O added is 2 mmol, and the rest of the conditions are exactly the same.

[0043] Examples 1, 5-6, and Comparative Examples 1-2 explore the effect of the molar ratio of cobalt salt to zinc salt on the reaction, and the results are shown in Table 1.

[0044] Table 1, Experimental results under different molar ratios of cobalt salt to zinc salt in S2

[0045] As can be seen from Table 1, different molar ratios of cobalt salt and zinc salt in S2 will lead to different experimental results. When the ratio is 1:25 or 1:50, the content of Co element is too high, which can form cobalt nanoparticles Co-NPs by self-aggregation, and cannot form high-dispersed metal site catalytic materials. When the molar ratio is 1:75~1:125, high-dispersed MnCo-CN can be formed. Since the catalytic performance of the material synthesized at a ratio of 1:75 is the best, this ratio is selected in the experiment.

Claims

1. A method for preparing a manganese / cobalt-supported nitrogen-doped carbon material, characterized in that: Includes the following steps: S1. Dissolve soluble zinc salt, soluble manganese salt and 2-methylimidazole in water, stir, centrifuge, wash and dry to obtain Mn-ZIF precursor; S2. The Mn-ZIF precursor obtained in S1 is dispersed in methanol, and a 2-methylimidazolium methanol solution and a mixed methanol solution of soluble zinc salt and soluble cobalt salt are added. After stirring, the mixture is subjected to crystallization reaction, separation, washing and drying to obtain Mn-ZIF@Co-ZIF bimetallic organic framework material. S3. Using Mn-ZIF@Co-ZIF as a template, high-temperature pyrolysis, acid washing, and centrifugal drying were performed to obtain manganese / cobalt-loaded nitrogen-doped carbon material MnCo-NC.

2. The method for preparing manganese / cobalt-supported nitrogen-doped carbon material according to claim 1, characterized in that: In S1, the molar ratio of soluble zinc salt to 2-methylimidazole is 1:6; the molar ratio of manganese salt to zinc salt is 1:

100.

3. The method for preparing manganese / cobalt-supported nitrogen-doped carbon material according to claim 1, characterized in that: The reaction temperature in S1 was 25℃; the stirring time was 2 hours.

4. The method for preparing manganese / cobalt-supported nitrogen-doped carbon material according to claim 1, characterized in that: The molar ratio of cobalt salt to zinc salt in S2 is 1:75 to 1:

125.

5. The method for preparing manganese / cobalt-supported nitrogen-doped carbon material according to claim 1, characterized in that: The ratio of ZIF-L(Mn) precursor to 2-methylimidazole was 0.1 g: 3 mmol.

6. The method for preparing manganese / cobalt supported nitrogen-doped carbon material according to claim 1, characterized in that: The reaction temperature in S2 was 25℃; the stirring time was 20 min; and the crystallization reaction time was 24 h.

7. The method for preparing manganese / cobalt-supported nitrogen-doped carbon material according to claim 1, characterized in that: The high-temperature pyrolysis atmosphere described in S3 is nitrogen or argon; the pyrolysis temperature is 850–1000℃; the heating rate is 3–7℃ / min; and the holding time is 2–5h.

8. A manganese / cobalt-loaded nitrogen-doped carbon material prepared by any one of the preparation methods in claims 1-7.

9. The application of a manganese / cobalt-supported nitrogen-doped carbon material prepared by any one of the preparation methods in claims 1-7 as a catalyst in photocatalytic CO2 reduction.